Efektivitas Taktik Pengaruh dalam Kepemimpinan: Perspektif Etika, Budaya, dan Gender - Maulan Aklil; Panca Tuah (Journal of Knowledge Management, 2025)
Influence tactics are a crucial aspect of leadership because they determine how a leader shapes the behavior, attitude, and commitment of followers. However, the effectiveness of the use of influence tactics cannot be separated from the ethical, cultural, and gender dimensions that frame interactions within organizations. This research is important because there is still a lack of comprehensive studies that integrate these three dimensions in evaluating the legitimacy and success of influence tactics. The aim of this study was to analyze how nine influence tactics can be understood and accepted in the perspective of ethical values, cultural norms, and gender construction. The method used is qualitative-based literature study, by examining scientific literature from journals, books, and relevant research. The results of the study show that rational persuasion, consultation, and inspirational pleas are the most ethical and effective tactics. Instead, pressure, licking, and coalitions have the potential to lead to manipulation, psychological pressure, and organizational resistance. Cultural preferences affect acceptance of certain tactics, while gender bias influences perceptions of female leaders' influence styles. The contribution of this article is to offer a framework for evaluating influence tactics that are more contextual and ethical, as well as providing practical direction for the development of more inclusive, adaptive, and sustainable leadership in multicultural and digital organizations.